Characterization of antimicrobial resistance genes of E. coli isolates from chicken broilers in commercial production in India - Lim, Ye Joon (Nanyang Technological University, 2023)
There are limited studies on whole genome sequencing (WGS) of Escherichia. coli isolated from chicken in India. As a popular foodborne pathogen, E. coli is also known to be carriers of antimicrobial resistance gene (ARG) and could facilitate the transmission of ARG between humans and chickens. WGS provides a bias-free approach for ARG detection. This study aimed to investigate the antimicrobial resistance (AMR) patterns of E. coli strains isolated from broilers in India. In total, 43 E. coli strains were sent for WGS. Raw sequenced data were assembled using SPAdes and analyzed using Multilocus sequence typing (MLST), PlasmidFinder and ResFinder tools to determine sequence type (ST), plasmid replicon sequences and ARG, respectively. Sequenced isolates revealed 10 different STs, with ST 21 (n = 6) and ST 343 (n = 4) being the most prevalent. Of the 23 plasmid replicon types identified, the most common was IncFIB (AP001918) (n = 16). The tet (A) gene was found in most isolates (n = 32) and multiple aminoglycoside ARGs co-existed on a single isolate. Our findings suggest prevalence of isolates resistant to antimicrobials deemed to be of highest priority by the World Health Organization (WHO) and multidrug resistant (MDR) isolate in poultry production.